Catalytic Ugi Reactions: Current Advances, Future Challenges, Part 2 - BURKE, Anthony (2020)
Multicomponent reactions (MCRs) are a very important class of reactions that are considerably useful in the quest for new medicines and, within this category, the Ugi-MCR holds a special place. In part 2 of this series (the first was previously published) we discuss advances in the catalytic 3- and 4-component Ugi reactions (U-3-CR and U-4-CR, respectively) as regards to nanocatalysis, biocatalysis, asymmetric catalysis with organocatalysts, as well as continuous manufacturing methods such as, continuous-flow processes. Again, in this review there is a strong focus on green and sustainable versions of this important reaction. To conclude this report, the operation and implications (both presently and in the future) of this versatile and enabling reaction in the pharmaceutical industry are discussed.